Application of integrated resource management tools: Decision support for small ruminant dairy Mediterranean farming systems - Ruiz R.; González Estrada E.; Oregui L.; Herrero M. (L'évolution des systèmes de production ovine et caprine : avenir des systèmes extensifs face aux changements de la société, 2004)
Small ruminant systems in the Mediterranean basin are conditioned by many constraints. Dairy farmers have to develop specific managerial strategies and practices aimed at increasing the profitability and sustainability of the system, and adjust to new political guidelines. The main objective of this work is to present the application of a decision-support system (DSS) for the integrated analysis of farming systems in the Mediterranean basin. The core of the methodology consists of the integration of: (i) simulation models of biological processes; (ii) a geographical information system (GIS); and (iii) a multiple-criteria optimisation model. This DSS aims to provide researchers, technical advisors and policy makers with an analysis tool that takes into account the dynamic biological, economic and social subsystems that operate at farm and regional level. The application of such DSS might guide the design of strategies that enhance the profitability and sustainability of small ruminant systems.
Séminaire du Sous-Réseau Systèmes de Production du Réseau Coopératif Interrégional FAO-CIHEAM de Recherche et Développement sur les Ovins et les Caprins, 2002/04/04-06, Alghero (Italy)